Removal of selected pharmaceuticals by sulfur-doped graphitic carbon nitride-polysulfone (PSf-S-g-C3N4) membranes: Mechanisms and antifouling properties - Oranso T. Mahlangu; Samkeliso S. Ndzimandze; Gcina D. Vilakati; Gcina Mamba; Bhekie B. Mamba (Desalination and Water Treatment)
This work probed the potential application of polysulfone (PSf) membranes incorporated with sulfur-doped graphitic carbon nitride (S-g-C3N4) nanosheets for the removal of five pharmaceuticals recently detected in major water sources in South Africa. The S-g-C3N4 was added to enhance pharmaceutical rejection as well as fouling prevention by increasing the electron donor components of the membranes which increases the membrane hydrophilicity. The PSf-S-g-C3N4 membranes were fabricated through a non-solvent induced phase separation (NIPS) approach, and their physicochemical properties were studied using advanced techniques including SEM, AFM, FT-IR, goniometer and SAXSpace. Further, rejection and antifouling properties were determined using salts, pharmaceuticals and humic acid. Adding S-g-C3N4 resulted in more finger-like micro voids and bulges on the membranes. This translated to an increase in membrane surface roughness (9.3–20.4 nm). Moreover, there was improvement in membrane porosity (20–35 %), permeability (∽0.5–4.3 Lm−2h−1bar−1), and mechanical properties. The increase in water permeability was due to the membranes becoming more hydrophilic with S-g-C3N4 addition (79–70 °). Overall, adding S-g-C3N4 improved the rejection of efavirenz (20–60 %), ibuprofen (19–36 %), naproxen (38–58 %), sulfamethoxazole (68–75 %) and trimethoprim (7–38 %) compared to the neat PSf membrane. Finally, S-g-C3N4 addition induced antifouling properties (FRR ˃ 80 %) and improved NOM removal (˃97 %). The membranes have great potential as a polishing step for pharmaceutical removal in wastewater and can be applied in water splitting and photocatalytic CO2 reduction due to the increased charge density and reduced energy band gap of S-g-C3N4 through the substitution of nitrogen sites.